Інноваційний підхід до формування управлінської структури на основі холакратії - Хабалевський, В. А. (ТОВ "ДКС Центр", 2024)
Горизонтальна структура управління або «холакратія» - це відносно нова світова тенденція. Основою такої структури є: команди, які самоорганізуються, відсутність поділу на ієрархічні рівні, децентралізація управління підрозділами компанії. За цієї структури прискорюється прийняття управлінських рішень, зменшується кількість менеджерів середньої ланки, скорочується бюрократія, тощо. Співробітники отримують більше можливостей для ініціативи, а їх вплив на бізнес-процеси зростає, при цьому керівництво ставить тільки стратегічні цілі. Головним завданням холакратії є пошук самостійного, ініціативного і мотивованого персоналу, здатного ефективно працювати в команді «без контролю». До такої структури управління прагнуть багато IT-компанії, роздрібні мережі, банки, тощо. Тому, особливої актуальності набуває процес формування управлінської структури на основі холакратії і розробка рекомендацій щодо використання такої структури для підвищення ефективності роботи команди.

Horizontal management structure or "holacracy" is a relatively new global trend. The basis of such a structure is: self-organizing teams; lack of division into hierarchical levels; decentralization of management of the company's divisions. Under this structure, managerial decision-making is accelerated, the number of middle managers and bureaucracy is reduced, etc. Employees get more opportunities for initiative, and their influence on business processes increases, while management sets only strategic goals. The main task of holacracy is to find independent, proactive and motivated personnel who are able to work effectively in a team "without control". It should also be noted that this approach to team formation enables teams to quickly adapt to current challenges and this provides additional competitive advantages in modern business. Adaptability can be achieved by changing roles in circles. This possibility exists due to the fact that, according to the principles of holacracy, one worker can have several roles at the same time, and therefore it is possible to dynamically change them during the executive process and thus quickly adapt to current challenges, which in turn will lead to an increase in the quality of team management and will allow to achieve the set goals of the project in a faster time, and this will also increase the competitive ability of the enterprise, which is a very important fact in modern business. In addition, we can note that modern methods of project management such as Agile, Scrum, Kanban can be effectively used in such a type of team management as holacracy and their combined use will allow to obtain a synergistic effect. which consists in the presence of a common goal instead of a set of individual ones; a sense of community and trust instead of loneliness and alienation; cooperation instead of competition; working for a common result and achieving team goals and organizational goals; creativity instead of stereotypical actions, which in turn will be able to ensure the achievement of results in a shorter period. Many IT companies, retail chains, banks, etc., strive for such a management structure. Therefore, the process of forming a management structure based on holacracy and the development of recommendations for the use of such a structure to increase the effectiveness of the team's work acquires special relevance.
Innovative approach to the formation of a management structure based on holacracy
Keywords: холакратія; холархія; бірюзові організації; проєктний менеджмент; формування проєктних команд; організаційна структура; управління персоналом; управління проєктами; holacracy; holarchy; turquoise organizations; project managemen; formation of project teams; organizational structure; personnel management; project management